2022
DOI: 10.1200/jco.2022.40.16_suppl.7527
|View full text |Cite
|
Sign up to set email alerts
|

Epcoritamab (epco) with gemcitabine + oxaliplatin (GemOx) in patients (pts) with relapsed or refractory (R/R) diffuse large B-cell lymphoma (DLBCL) ineligible for autologous stem cell transplant (ASCT) induces high response rate even in pts failing CAR T therapy.

Abstract: 7527 Background: Pts with R/R DLBCL who fail or are ineligible for ASCT have very poor outcomes with standard palliative chemotherapy. Rituximab + GemOx had a complete response rate of 33% (Cazelles et al, Leuk Lymphoma 2021); novel approaches are needed. Epco is a subcutaneously administered bispecific antibody targeting CD3 on T cells and CD20 on B cells. In the EPCORE NHL-1 dose-escalation trial, epco had manageable safety and antitumor activity in heavily pretreated B-cell NHL including DLBCL. EPCORE NHL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Glofitamab and epcoritamab have been integrated into standard-of-care platinum-based chemoimmunotherapy platforms for the treatment of patients with R/R aNHL. Clinical results have been promising (eg, ORR and CR rate of 100% and 86%, respectively, for epcoritamab-R-DHAX, 62 and 92% and 60%, respectively, for epcoritamab-gemcitabine, oxaliplatin 63 ) and registration-directed phase 3 trials are being launched (supplemental Table ).…”
Section: Bsab-containing Combinationsmentioning
confidence: 99%
“…Glofitamab and epcoritamab have been integrated into standard-of-care platinum-based chemoimmunotherapy platforms for the treatment of patients with R/R aNHL. Clinical results have been promising (eg, ORR and CR rate of 100% and 86%, respectively, for epcoritamab-R-DHAX, 62 and 92% and 60%, respectively, for epcoritamab-gemcitabine, oxaliplatin 63 ) and registration-directed phase 3 trials are being launched (supplemental Table ).…”
Section: Bsab-containing Combinationsmentioning
confidence: 99%
“…These include combinations with platinum‐based chemoimmunotherapy for r/r aggressive B‐cell lymphomas, including DLBCL. Clinical results are so far quite favourable, with manageable toxicity and response rates of 90%–100% for the combinations of epcoritamab + R‐DHAX (rituximab, dexamethasone, cytarabine, oxaliplatin), 24 epcoritamab + GemOx (rituximab, gemcitabine, oxaliplatin), 25 as well as glofitamab + R‐GemOx. A randomised phase 3 study of GemOx +/− glofitamab is ongoing as well as a randomised phase 3 study of epcoritamab versus standard of care (R‐GemOx or R‐bendamustine) 26,27 .…”
Section: Combination Studiesmentioning
confidence: 99%
“…Tnb-486, a novel CD3xCD19 BiAb, demonstrated a complete response in 91% of RRFL patients in a phase 1 trial and had a lower incidence of ICANS and CRS compared to blinatumomab [ 119 , 121 , 123 ]. Mechanistically, the lower incidence of ICANS and CRS associated with Tnb-486 is likely due to its unique anti-CD3 moiety, designed to bind CD3 on T cells with low affinity, thereby attenuating the release of pro-inflammatory cytokines [ 124 ]. The higher incidence of ICANS observed with CD19xCD3 BiAbs when compared to CD3xCD20 BiAbs may be due to potential on-target off-tumor toxicity associated with targeting CD19, which is expressed on the pericytes and vascular smooth muscles that line the blood–brain barrier (BBB); therefore, the use of anti-CD19 BiAbs such as blinatumomab may impair the integrity of the BBB [ 125 ].…”
Section: Bispecific T-cell Engagers and Antibodies In The Treatment O...mentioning
confidence: 99%
“…In this regard, gemcitabine can upregulate CD20 on DLBCL cells in vitro, which enhances the antitumor activity of rituximab [ 127 ]. A recent phase Ib/II trial demonstrated that epcoritamab + GemOx (gemcitabine, oxaliplatin) in RR DLBCL displayed a higher ORR than epcoritamab monotherapy (92% vs. 63%) [ 111 , 124 ]. Moreover, ameliorating antigen escape through targeting multiple antigens simultaneously in NHL may provide a novel approach to enhance their efficacy [ 113 , 128 ].…”
Section: Bispecific T-cell Engagers and Antibodies In The Treatment O...mentioning
confidence: 99%